(untitled) (International journal of artificial intelligence, 2026)
Thanks to independence, major reforms are also being carried out in the field of education. From the first days of independence, serious attention has been paid to the education of the younger generation. The introduction of the Law "On Education", the "National Program for Personnel Training", and the "State Educational Standards" are characterized as the most important stages in these processes. These documents also set a number of requirements for native language education. On this basis, native language programs and textbooks were also updated. Two generations of updated native language textbooks were published and introduced into teaching. Views and requirements for teaching the native language have changed. Textbooks were compiled based on these requirements. This article provides information about the methodology for teaching the Uzbek language.